Sexual Dimorphism in Total Length of Fully Ossified Dry Human Left Tibia - Akter, Mahbuba; Zaman, Fahmida; Tania, Israt Jahan; Fahmi, Soniya; Any, Omma Hafsa (Journal of Current and Advance Medical Research, 2018)
Background: Determination of sex from skeletal remains is one of the important aspects of Osteometric analysis. Objectives: The present study was planned to collect data regarding total length of fully ossified dry human left tibia and to find out possible variations in male and female. Methodology: This analytical type of cross-sectional study was conducted in the Department of Anatomy at Sir Salimullah Medical College, Dhaka, Bangladesh from July 2014 to June 2015 for a period of one year. In this study fully ossified dry human left tibia of unknown sex were collected from In this study fully ossified dry human left tibia of unknown sex were collected from the department of Anatomy and also from the students of Sir Salimullah Medical College (SSMC), Dhaka, Ibrahim Medical College (IMC), Dhaka, Dhaka National Medical College (DNMC), Dhaka and Bangladesh Medical College (BMC), Dhaka. The study samples were distributed in male and female sex groups by discriminate function analysis. Total lengths were measured with the help of an osteometric board. Results: A total number of two hundred (200) fully ossified dry human left tibia of unknown sex were analyzed. The mean (±SD) values of total length were greater in male (38.82 ± 2.94) cm than female (33.48 ± 1.68) which was statically significant (p< 0.001). Conclusion: In conclusion the total length is greater in male compared to female. Journal of Current and Advance Medical Research 2018;5(1):7-10